Implementasi Nilai-nilai Pesantren dalam Memebentuk Karakter Siswa MA Al-Islamiyah Danawarih : Implementation of Islamic Boarding School Values in Shaping Student Character MA Al-Islamiyah Danawarih - Aula, Afikatul; Khaerunisa, Ainun; Isnan Syihabul Millah, Muhamad; Maftuhi, Muhammad; Fitriah (ISEDU : Islamic Education Journal, 2024)
The purpose of this study is to find out the best way to take character education, as well as the difficulties faced and the solutions used. The research was conducted at MA al Islamiyah Danawarih using qualitative methodologies and data collection techniques such as observation, interview, and documentation. As a result, character education values are implemented through conceptual knowledge, following rules, and modeling good behavior-all of which continue to support each stage of the character education process. This process still faces internal and external obstacles despite these efforts. Appropriate solutions are needed to overcome these challenges, such as reminding teachers and encouraging continuous introspection from both students and teachers engaged in character education.